Corporate Social Responsibility in the Practice of Public Relations Professionals (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
Are public relations a socially irresponsible profession? Although the image of public relations professionals can still be negative, in theory, they should help their organizations be socially responsible. This paper aims to explore the work of public relations experts concerning corporate social responsibility among those who work for successful retail chains in Croatia. The research paper resides on a survey conducted by the method of in-depth interviews with seven corporate communications managers selected among the 20 best retailers in the fast-moving consumer goods on the Croatian market. The research showed that the surveyed public relations experts are not directly in charge of the strategic planning of their companies socially responsible business programs. However, most respondents confirmed the existence of a communication strategy for CSR activities regarding different stakeholders.  Besides, the results show that the heads of the communications department daily participate at the executive level of socially responsible programs. These results are showing that those corporate communications managers are generally not members of senior management, where decision-making takes place. Finally, the conclusion is that the surveyed public relations experts in their practical work mainly help their companies to be socially responsible.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.